PENGARUH BELANJA DAERAH KABUPATEN/KOTA TERHADAP PERTUMBUHAN EKONOMI DAN KESEJAHTERAAN MASYARAKAT DI PROVINSI SULAWESI TENGAH TAHUN 2013 – 2017 - Muthahar, La Ode Muhammad; Tenge, Erna; Sading, Yunus (Katalogis, 2021)
This research aims tp determine the direct influence of Employee Spending, Capital Spending, Goods and Services Spending, Grant Spending, and Social Assistance Spending on Economic Growth and Community Welfare and the indirect effect of Employee Spending, Capital Spending, Spending on Goods and Services, Grant Spending, and Social Assistance Spending for Community Welfare through Economic Growth. The analytical method used in this research is Partial Least Square (PLS). The results of the study found that: Direct Influence (1) Employee Spending, Capital Spending have a significant effect on economic growth while Spending on Goods and Services, Grant Spending and Social Assistance Spending don’t have a significant effect on Economic Growth; 2) Employee Spending, Grant Spending and Social Assistance Spending have a significant effect on the walfare of the community while Capital Spending and Spending on Goods and Services don’t have a significant effect on community Welfare; Indirect Influence: Employee Spending, Capital Spending, Goods and Services Spending, Grant Spending, and Social Assistance Spending have a significant effect on Community Welfare through Economic Growth. Regional Government needs to position Regional Spending in produvtive activities and on target as well as the need for budget efficiency from official travel funds that can be diverted for capital spending.